Precision Pharmacy in Hematology: Integration of Pharmacogenomics into Clinical Decision-Making in Anticoagulant and Chemotherapeutic Agents - Thubab, Riyad Yahya; Madkhali, Hafed Mohammed; Assiri, Hassan Omar (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">: Precision pharmacy, driven by pharmacogenomics, personalizes anticoagulant and chemotherapeutic therapy based on the genetic profile of the patient, which enhances the outcome of therapy in hematologic diseases. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review attempts to address the integration of pharmacogenomics into decision-making regarding anticoagulants and chemotherapeutics in hematology with special reference to the pharmacist. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Systematic review of literature using PubMed, Scopus, and Web of Science was conducted for studies between the years 2020-2024. Selection criteria focused on pharmacogenomic applications in hematology. Data were integrated to identify key gene-drug interactions, implementation strategies in clinics, and hindrances. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pharmacogenomic testing of <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">CYP2C9<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">/<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">VKORC1<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> for warfarin dosing reduced bleeding events by 15%, while <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">TPMT<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">/<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-style: italic; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">NUDT15<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> testing for thiopurines reduced myelosuppression by 25%. Clinical decision support systems (CDSS) and proactive testing, like the PHASER program, improved outcomes by 12–18%. Limitations involve cost, availability, and clinician training constraints. <span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: 'Times New Roman', serif; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Pharmacogenomics improves the safety and efficacy of anticoagulant and chemotherapeutic treatment in hematology, with pharmacists as central implementers. Continued advances in AI and multi-omics will progressively optimize precision pharmacy.